О фауне и экологии пауков окрестностей Канева (Лесостепь УССР) - Пичка, В.Е. (Вестник зоологии, 1974)
The article deals with the results of processing of spider collection gathered by the author in forest-steppe zone of the Ukrainian SSR (in the Kanev environs). A list and distribution by habitats of 124 species and variations of spiders are presented. 35 species are mentioned for the forest-steppe zone of the Ukrainian SSR for the first time.